2008
DOI: 10.1007/s11418-008-0283-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Curcuma plants and curcumin content level by DNA polymorphisms in the trnS-trnfM intergenic spacer in chloroplast DNA

Abstract: With the goal of developing an accurate plant identification method, molecular analysis based on polymorphisms of the nucleotide sequence of chloroplast DNA (cpDNA) was performed in order to distinguish four Curcuma species: C. longa, C. aromatica, C. zedoaria, and C. xanthorrhiza. Nineteen regions of cpDNA were amplified successfully via polymerase chain reaction (PCR) using total DNA of all Curcuma plants. Using the intergenic spacer between trnS and trnfM (trnSfM), all four Curcuma plant species were correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Normally, the content of curcumin in C. longa is about 10-fold of that of C. aromatica . On the other hand, C. aromatica has much more essential oil components than C. longa [6]. Some essential oil components, such as β -bisabolene, β -sesquiphellandrene and ar-curcumene have been reported and it was showed that these essential oils exhibited multiple biological activities [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, the content of curcumin in C. longa is about 10-fold of that of C. aromatica . On the other hand, C. aromatica has much more essential oil components than C. longa [6]. Some essential oil components, such as β -bisabolene, β -sesquiphellandrene and ar-curcumene have been reported and it was showed that these essential oils exhibited multiple biological activities [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…This marker is sensitive to experimental conditions of the polymerase chain reaction (PCR) because judgment is based on the presence or absence of PCR products. In addition, Minami et al [4] reported that Curcuma species can be identified using an intergenic spacer between trnS and trnfM of chloroplast deoxyribonucleic acid (cpDNA). Although this method is useful for identifying C. longa from various Curcuma rhizomes, the study by Minami et al [4] may require re-evaluation since the number of sample species used were few, and it did not employ appropriate outgroup taxa.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Minami et al [4] reported that Curcuma species can be identified using an intergenic spacer between trnS and trnfM of chloroplast deoxyribonucleic acid (cpDNA). Although this method is useful for identifying C. longa from various Curcuma rhizomes, the study by Minami et al [4] may require re-evaluation since the number of sample species used were few, and it did not employ appropriate outgroup taxa. The same can be said of the study by Sasaki et al [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical profiling of the essential oils (Karig, 1975;Sen, Sen Gupta, & Ghosh Dastidar, 1974;Zwaving & Bos, 1992) for differentiating adulterant Curcuma species is also subjective as the adulterant species closely resemble the genuine material and many extrinsic factors such as methods of cultivation, harvesting, drying and storing may affect the ultimate chemical profile of turmeric. Though many workers have demonstrated the efficacy of molecular markers for identifying turmeric adulteration in planta (single nucleotide polymorphism developed by Cao et al (2001), Komatsu and Cao (2003), Sasaki et al (2004) and Minami et al (2009)), the suitability of these methods to detect adulteration in traded turmeric powder is yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleic acid analysis represents a good alternative to these conventional methods and is very useful for detecting the plant based adulterants in traded plant materials (Lum & Hirsch, 2006). Although a few reports based on molecular techniques are available for the identification of turmeric in planta (C. longa) from other related species (Cao, Sasaki, Fushimi, & Komatsu, 2001;Komatsu & Cao, 2003;Minami et al, 2009;Sasaki, Fushimi, & Komatsu, 2004) no reports are available on adulterant detection in marketed turmeric powder except the report of Sasikumar et al (2005) using RAPD markers. Here, we report a more reliable and Food Research International 44 (2011) 2889-2895 2.…”
Section: Introductionmentioning
confidence: 99%